Coping Mechanisms Of Information Technology Students During The New Normal - Virginia Natividad-Franco; Archie Nel B. De Jesus (Green Publisher Indonesia, 2022)
Information Technology (I.T.) and the net have transformed people's approach to life and educational access. These changes brought pressures and challenges to students to adapt to the new normal. The study aimed to determine the coping mechanisms of the I.T. students during the new normal era. The study utilized a mixed-methods type of research, which develops a novel theoretical perspective by combining the strengths of quantitative and qualitative methods. The study's respondents are the 515 students from the College of Information and Communications Technology at Bulacan State University, Philippines. A validated survey instrument was disseminated through messenger to randomly selected students in the college. Furthermore, a focus group discussion with the college organization officers was done via google meet. The findings revealed a 3.27 weighted mean on their coping behavior, which means that the Information and Technology students experienced this behavior sometimes. Moreover, to cope up with the challenges in the new normal education, the coping mechanisms they did enable them to survive in their studies are time management, self-determination, giving oneself to rest and to relax through mobile games, communicating with friends. Lastly, change of environment. Furthermore, appropriate behavior in managing the stress brought by the new normal education will make studying lighter and enjoyable. Recommendations as regards coping mechanisms were submitted to the administrators to further.